2008
DOI: 10.2137/145960609788066843
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in oats (Avena sativa L.) grown on acid sulphate soils

Abstract: The aim of the study was to investigate the impact of soil chemistry on the concentrations of Co, Ni, Zn, Mn, Cu and Fe in oats (Avena sativa L. cv. Fiia) grown on Finnish acid sulphate (AS) soils with varying geochemical characteristics. Twenty two soil profiles, which were sampled to a depth of 1 m (five 20 cm section splits), and 26 composite oat grain samples were collected on a total of five fields. The concentrations of Co, Ni, Zn and Mn in the grains were correlated with the NH 4 Ac-EDTA-extractable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
2
4
0
Order By: Relevance
“…The acidity and sulphate in all fields sampled in the present study increased markedly with descending depth from 0 to 100 cm and then decreased rapidly with descending depth from 100 to 140 cm, which is a common phenomenon in ASS used for agriculture (Mathew et al 2001;Boman et al 2010). The higher pH values obtained in the plough layer are a result of leaching, liming and a relatively higher organic matter concentration (Boman et al 2008), and the decreasing soil pH in deeper layers is a feature of the ASS used for cultivation, caused by the oxidation of sulphides (Faltmarsch et al 2009).…”
Section: Discussionsupporting
confidence: 58%
“…The acidity and sulphate in all fields sampled in the present study increased markedly with descending depth from 0 to 100 cm and then decreased rapidly with descending depth from 100 to 140 cm, which is a common phenomenon in ASS used for agriculture (Mathew et al 2001;Boman et al 2010). The higher pH values obtained in the plough layer are a result of leaching, liming and a relatively higher organic matter concentration (Boman et al 2008), and the decreasing soil pH in deeper layers is a feature of the ASS used for cultivation, caused by the oxidation of sulphides (Faltmarsch et al 2009).…”
Section: Discussionsupporting
confidence: 58%
“…2). This is consistent with an earlier study showing generally similar mean micronutrient concentrations in oat grains cultivated on five AS soils, but clearly enriched contents in oats in one of these fields as compared to the FAV (Fältmarsch et al, 2009). The concentrations of Ni and Mn in cabbage were not correlated to those in the topsoil of F1-F3 and lower than those of the FAV (Fig.…”
Section: Cobalt Nickel Zinc and Manganesesupporting
confidence: 92%
“…Our present knowledge on the chemical com-position of AS soil-grown crops is mainly based on a few publications (Palko, 1986;Yli-Halla and Palko, 1987) only, which showed significantly elevated concentrations of a number of metals in timothy grass and oat grains. However, a recent study showed that the metal concentrations in oats grown on AS soils were not in general elevated compared with average values on other soils (Fältmarsch et al, 2009), although anomalous concentrations were observed in one of the studied AS soils. The lack of sufficient information on metal concentrations in crops and vegetables grown on AS soils is thus evident.…”
Section: Introductionmentioning
confidence: 62%
“…The acid sulfate soils are, in contrast to the black shale soils, developed in soft sediments deposited in brackish or saline waters (mostly during Holocene) and containing disseminated sulfides produced by seawater sulfate reduction (Boman et al 2008). The two soil types thus have different direct origins and sulfur sources, but like the black shale soils, the acid sulfate soils have a chemistry dominated by sulfide oxidation, metal release, and acidification (Å ström 1998; Burton et al 2006a) and thus behave, in an environmental context, in a manner similar to the black shale soils (Macdonald et al 2007;Burton et al 2006b;Fältmarsch et al 2008Fältmarsch et al , 2009Boman et al 2010). Because both soil types are characterized by high contents of easily mobilized metals, the soil layers and downstream waters are all characterized by acidification and metal loadings (Å ström and Björklund 1995;Nordmyr et al 2008;Å ström et al 2010).…”
Section: Risks Associated With Metal-rich Soilsmentioning
confidence: 99%